Innovative Eco-Enzyme from Fruit and Vegetable Waste for Pollution Control - Ranno Rachman; Suci April Yanti; Nurjannah Oktorina Abdullah (Gema Lingkungan Kesehatan, 2025)
Eco-enzyme is a fermentation product that uses organic waste as a base material in addition to sugar and water. The fermentation process is carried out under anaerobic conditions with the help of microorganisms from organic materials, producing a valuable liquid as an environmentally friendly pesticide, such as a termite repellent. This study aims to determine eco-enzyme characteristics made from vegetable and fruit waste with palm sugar and sap substrates. The main parameters observed include pH, aroma, color, and acetic acid content to determine the relationship between parameters and the effectiveness of eco-enzyme as a termite repellent. This quantitative and qualitative research method has an experimental approach and theory development. The experiment was conducted by fermenting a mixture of organic waste, sugar, and water in a ratio of 1:3:10 for 90 days. The variations tested involved using two substrates: palm sugar and sap. The results showed that eco-enzyme with palm sugar substrate had a pH of 2.5–3.99, a typical sour aroma of palm sugar, a brownish color, and an acetic acid content of 4–5%. In contrast, eco-enzyme with sap substrate has a pH of 3.71–4.07, a distinctive aroma of sap, a yellowish color, and an acetic acid content of 1–2%. Based on these results, eco-enzyme made from palm sugar is more effective as a termite repellent because its acetic acid content is higher and corrosive, which can affect the development of termite organs. In addition, this eco-enzyme is easily decomposed in the environment and is safe to use because its acetic acid content is at a level that meets the SNI: 01-3711-1997 standard. Thus, eco-enzymes from palm sugar can be an environmentally friendly alternative for pest control.